"It's so hard taking pills when you don't know what they're for": a qualitative study of patients' medicine taking behaviours and conceptualisation of medicines in the context of rheumatoid arthritis - Boitshoko Kobue; Shirra Moch; Jennifer Watermeyer (BMC, 2017)
Abstract Background Patients with chronic illnesses are often required to take lifelong medication to alleviate symptoms and prevent disease progression. Many patients find it difficult to adhere to prescribed medication for various reasons, some of which may link to the way they conceptualise medicines and understand their illness and treatment. This study explores the medicine taking behaviours of patients presenting with Rheumatoid Arthritis (RA), a chronic inflammatory autoimmune disease. We focused particularly on patients' conceptualisation and understanding of medicines within this disease context, against a backdrop of scarce healthcare resources. Methods We conducted semi-structured interviews with 18 female patients at a rheumatology clinic in South Africa, as well as a review of participants' medical records. We conducted a secondary analysis of the data using thematic analysis and framework analysis principles. Results Participants reported a range of medicine taking behaviours including self-medicating, adding complementary and alternative medicines (CAM) or traditional remedies, and sometimes acquiring prescribed medicines illegally. Participants provided insights into their understanding of what constitutes a medicine and what substances can be added to a prescribed regimen, which impacted on adherence. Importantly, the majority of participants demonstrated poor understanding of their illness, medications, regimens and dosage instructions. Conclusions Medicine taking in the context of RA, within the studied demographic, is complex and appears strongly mediated by individual and contextual factors. Poor patient understanding, individual conceptualisation of medicines and medicine taking, and the availability of a range of additional medicines and remedies impact on adherence. Based on these findings, we make some suggestions for how healthcare providers can play a greater role in educating patients living with RA about medicines, CAM and traditional remedies, as well as medicine taking behaviours.